Low-Sulfidation Epithermal Carbonate-Base metal-Gold Mineralization Hosted by Tertiary Sedimentary Rocks in Bastem Prospect, Luwu District, Sulawesi Island, Indonesia: A Preliminary Study - Arifudin Idrus; Irzal Nur; Sufriadin Sufriadin; Fadlin Fadlin; Indra Sanjaya; Rohaya Langkoke (Journal of Applied Geology, 2020)
In Indonesia, gold is typically mined out from epithermal, porphyry and skarn deposit types occurred within volcanic belts along magmatic arc or active continental margin setting. Numerous gold prospects, however, are recently discovered in association with metamorphic and sedimentary rocks. This paper is aimed to discuss a preliminary study on the occurrences and characteristics of the sedimentary rock-hosted low-sulfidation (LS) epithermal gold mineralization in Bastem (Bessengan Tempe) prospect, Luwu district, Sulawesi Island, Indonesia. Detailed geological and hydrothermal alteration mapping was performed to understand the distribution and characteristics of ore mineralization. Representative ore samples taken were analysed for ore chemistry by means of Fire Assay – Atomic Absorption Spectrometry (FA-AAS) and Acid Geochemical Digest - Atomic Absorption Spectrometry (GA-AAS). The results from this work that the Bastem prospect is stratigrapically occupied by Tertiary sedimentary rocks of Toraja formation, which is adjacent to volcanic rocks of Lamasi formation. Gold-bearing quartz±carbonate veins are hosted by mudstone and siltstone of Toraja formation. The quartz-carbonate veins show a typical LS epithermal open space filling texture containing erratic gold grade of up to 7.16 g/t with relatively high besemetals (Pb and Zn) grades of up to >0.4 and >1%, respectively. Based on those various features, the LS epithermal deposit is categorized as “carbonate-basemetal-gold mineralization type”, which might be originated in back arc rift/basin setting. This ‘unconventional’ sedimentary rock hosted-gold mineralization type would be the new target of gold exploration in Indonesia.